Commonality in hedge fund returns: driving factors and implications - Matthieu Bussière; Marie Hoerova; Benjamin Klaus (European Central Bank (ECB), 2014)
We measure the commonality in hedge fund returns, identify its main driving factor and analyse its implications for financial stability. We find that hedge funds' commonality increased significantly from 2003 until 2006. We attribute this rise mainly to the increase in hedge funds' exposure to emerging market equities, which we identify as a common factor in hedge fund returns over this period. Our results show that funds with a high commonality were affected disproportionately by illiquidity and exhibited negative returns during the subsequent financial crisis, thereby providing little diversification benefits to the financial system and to investors.
Keywords: G01; G10; G11; G23; 330; commonality; financial crisis; hedge funds; liquidity; risk factors